STRATEGI BISNIS DAN KEUNGGULAN BERSAING TERHADAP KINERJA PEMASARAN USAHA KECIL MENENGAH KOPIAH RESAM MENTARI KOTA PANGKALPINANG - Pony Safitri; Zakia Fajrin (Faculty of Economics and Business, Universitas Malikussaleh, 2019)
The increasing competition in the business world require the entrepreneurs to do some qualified strategy, so they can reach sustainable competitive advantageand improve marketing performanceof company. The study aims to examine and analyze business strategy that current run, the influence of business strategy and compititive advantage on marketing performance both partialy and simultaneously, and also the oppropriate competitive strategy for the future. The study used quantitative method. Population of study is member of the group of craftsmen Kopiah Resam Mentari in west bangka Regency in the amount of 30 people. The study used sampling census techniques, so that allof member ofcraftsmenin used as sample.